Developing A Web-Based Learning Media On Maharoh Istima In MAN 1 Kota Kediri - Ma’arif, M. Syamsul; Fatkhurrahmah, Fiki (UIN Syekh Wasil Kediri, Indonesia, 2021)
The use of learning media on Maharoh Istima is very essential to promote students’ listening skills. Learning media used by teachers used to be ineffective due to the students’ heterogenous listening proficiency. That’s why, it is needed to develop an autonomous and flexible learning media to promote students’ listening skill which can be implemented anytime and anywhere. This Research and Development study employed a developmental method called ADDIE. The media produced was validated by media and material experts using a Likert Scale for analysis. The study produced a website http://belajaristima.com/ validated by the media expert in 92,30% and the material expert in 97,27 %. From the validation, it is said that the media is valid and can be implemented as a learning media.